Narrative Healing in Homeopathy: Dream Narration as Diagnostic and Therapeutic Value - Tarro, Giulio; De Giorgio, Giovanni (British Journal of Healthcare and Medical Research, 2026)
In homeopathic practice, dreams are not simply repertory symptoms or marginal details of the examination, but a form of language through which vital force is expressed. They are fragments of truth embedded in the individual’s constitution that emerge during sleep, when consciousness slackens and leaves room for what remains invisible and unheard in waking life. Narrating a dream is not simply explaining what was dreamed, but giving form to an internal movement of thought that, through narration, can become part of the healing process. Homeopathy integrates narratives into the healing process, a process that unfolds pharmacologically and narratively, and resonates with the essence of modern narrative medicine: healing also occurs through the stories the patient tells. We maintain that dreams, in addition to being a repertory symptom useful for identifying the "similar" or "simillimum" medicine, are also an amplifier of vital force and an adjuvant to homeopathic therapy when the narrative is consistent with the "law of similars." The theoretical results, which we have obtained using methods based on clinical reasoning and a rigorous interpretation of the fundamental principles of homeopathy, suggest that dreams can already be considered a symbolic homeopathic remedy, capable of evoking, intensifying, and healing contents similar to the patient’s reality, facilitating transformation and healing. We hope that this work, while theoretical, will foster future systematic and scientifically sound studies.